A meta-analysis reveals the effectiveness of probiotics and prebiotics against respiratory viral infection. Issue 3 (26th March 2021) - Wang, Fangyan; Pan, Binhui; Xu, Sheng; Xu, Zhihua; Zhang, Tiaotiao; Zhang, Qihao; Bao, Yifan; Wang, Yingwei; Zhang, Jiamin; Xu, Changlong; Xue, Xiangyang
Abstract: Experimental experience suggests that microbial agents including probiotics and prebiotics (representative microbial agents) play a critical role in defending against respiratory virus infection. We aim to systematically examine these agents' effect on respiratory viral infection and encourage research into clinical applications. An electronic literature search was conducted from published data with a combination of a microbial agents search component containing synonyms for microbial agents-related terms and a customized search component for respiratory virus infection. Hazard ratio (HR), risk ratio (RR) and standard deviation (SD) were employed as effect estimates. In 45 preclinical studies, the mortality rates decreased in the respiratory viral infection models that included prebiotics or prebiotics as interventions (HR: 0.70; 95% confidence interval (CI): 0.56–0.87; P =0.002). There was a significant decrease in viral load due to improved gut microbiota (SD: −1.22; 95% CI: −1.50 to −0.94; P <0.001). Concentrations of interferon (IFN)-α (SD: 1.05; 95% CI: 0.33–1.77; P =0.004), IFN-γ (SD: 0.83; 95% CI: 0.01–1.65; P =0.05) and interleukin (IL)-12 (SD: 2.42; 95% CI: 0.32–4.52; P =0.02), IL-1β (SD: 0.01; 95% CI: −0.37 to 0.40; P =0.94) increased, whereas those of TNF-α (SD: −0.58; 95% CI: −1.59 to 0.43; P =0.26) and IL-6 (SD: −0.59; 95% CI: −1.24 to 0.07; P =0.08) decreased. Six clinical studies had lower symptom scores (SD: −0.09; 95% CI: −0.44 to 0.26; P =0.61) and less incidence of infection (RR: 0.80; 95% CI: 0.64–1.01; P =0.06). Our research indicates that probiotics and prebiotics pose a defensive possibility on respiratory viral infection and may encourage the clinical application.